Regulation of fatty acid movement in human adipose tissue in the postabsorptive-to-postprandial transition. - Frayn, K; Shadid, S; Hamlani, R; Humphreys, S; Clark, M; Fielding, B; Boland, O; Coppack, S (1994)
There is net outward flow of fatty acids from adipose tissue in the fasted state but net inward flow and storage in the postprandial state. We investigated how this is regulated. Arteriovenous differences were measured across a subcutaneous adipose depot in six normal subjects before and for 5 h after a meal containing 80 g fat and 80 g carbohydrate. In five further experiments, insulin was infused at 40 mU.m-2.min-1 from 30 min after the meal, clamping the plasma glucose. Net transcapillary fatty acid flow changed from negative (outward flow from tissue to capillaries) in the postabsorptive state to consistently positive (net inward flow, implying fat storage) after the meal despite continued net efflux of fatty acids into venous blood. In the "clamped" experiments (with additional insulin), net fatty acid efflux in the venous blood was suppressed and positive transcapillary flux (storage) was more marked. Regulation of fatty acid flow appeared to depend on coordinated changes in hormone-sensitive lipase (HSL) and lipoprotein lipase (LPL) action and fatty acid esterification. Additional insulin caused no further suppression of HSL or activation of LPL but markedly stimulated fatty acid retention (presumed to represent esterification). In the absence of additional insulin, a high proportion of the fatty acids liberated by LPL are released into the venous plasma in both postabsorptive and postprandial states. We hypothesize that this "loss" of fatty acids is necessary to give precise control to the pathway of fat storage.